Centrally Determined Standardization of Flow Cytometry Methods Reduces Interlaboratory Variation in a Prospective Multicenter Study. Issue 11 (November 2017) - Westera, Liset; van Viegen, Tanja; Jeyarajah, Jenny; Azad, Azar; Bilsborough, Janine; van den Brink, Gijs R; Cremer, Jonathan; Danese, Silvio; D'Haens, Geert; Eckmann, Lars; Faubion, William; Filice, Melissa; et al.
Abstract : OBJECTIVES: : Flow cytometry (FC) aids in characterization of cellular and molecular factors involved in pathologic immune responses. Although FC has potential to facilitate early drug development in inflammatory bowel disease, interlaboratory variability limits its use in multicenter trials. Standardization of methods may address this limitation. We compared variability in FC‐aided quantitation of T‐cell responses across international laboratories using three analytical strategies. METHODS: : Peripheral blood mononuclear cells (PBMCs) were isolated from three healthy donors, stimulated with phorbol 12‐myristate 13‐acetate and ionomycin at a central laboratory, fixed, frozen, and shipped to seven international laboratories. Permeabilization and staining was performed in triplicate at each laboratory using a common protocol and centrally provided reagents. Gating was performed using local gating with a local strategy (LGLS), local gating with a central strategy (LGCS), and central gating (CG). Median cell percentages were calculated across triplicates and donors, and reported for each condition and strategy. The coefficient of variation (CV) was calculated across laboratories. Between‐strategy comparisons were made using a two‐way analysis of variance adjusting for donor. RESULTS: : Mean interlaboratory CV ranged from 1.8 to 102.1% depending on cell population and gating strategy (LGLS, 4.4–102.1%; LGCS, 10.9–65.6%; CG, 1.8–20.9%). Mean interlaboratory CV differed significantly across strategies and was consistently lower with CG. CONCLUSIONS: : Central gating was the only strategy with mean CVs consistently lower than 25%, which is a proposed standard for pharmacodynamic and exploratory biomarker assays.